2015
DOI: 10.3390/ijms16047753
|View full text |Cite
|
Sign up to set email alerts
|

Biological Mechanisms Underlying the Ultraviolet Radiation-Induced Formation of Skin Wrinkling and Sagging I: Reduced Skin Elasticity, Highly Associated with Enhanced Dermal Elastase Activity, Triggers Wrinkling and Sagging

Abstract: The repetitive exposure of skin to ultraviolet B (UVB) preferentially elicits wrinkling while ultraviolet A (UVA) predominantly elicits sagging. In chronically UVB or UVA-exposed rat skin there is a similar tortuous deformation of elastic fibers together with decreased skin elasticity, whose magnitudes are greater in UVB-exposed skin than in UVA-exposed skin. Comparison of skin elasticity with the activity of matrix metalloproteinases (MMPs) in the dermis of ovariectomized rats after UVB or UVA irradiation dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 52 publications
2
95
0
6
Order By: Relevance
“…On the other hand, elastase enzymatically breaks down elastins fibers, that together with collagen, are responsible for the mechanical properties of connective tissue (Antonicelli et al, 2007). In addition, Imokawa and Ishida (2015) demonstrated that both skin-aging and antiwrinkle effects are significantly correlated with decreased elastase activity. Because of the specific role of elastase in the inflammatory process, its inhibition by NannoG encourages its use in cosmetic products for irritated, reactive and/or senescent epidermis (Henriksen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, elastase enzymatically breaks down elastins fibers, that together with collagen, are responsible for the mechanical properties of connective tissue (Antonicelli et al, 2007). In addition, Imokawa and Ishida (2015) demonstrated that both skin-aging and antiwrinkle effects are significantly correlated with decreased elastase activity. Because of the specific role of elastase in the inflammatory process, its inhibition by NannoG encourages its use in cosmetic products for irritated, reactive and/or senescent epidermis (Henriksen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1,8 The age dependent downregulation of skin elastic properties is not only attributed to a decreased synthesis of these proteins, but also to an upregulation of the corresponding proteinases. 26,27 Elastase, a member of the chymotrypsin family of serine proteinases is mainly responsible for the degradation of elastin. 7 Hyaluronic acid is degraded by another serine proteinase -hyaluronidase whereas collagenase a zinc containing matrix metalloproteinase hydrolyzes collagen.…”
Section: Anti -Aging Activitymentioning
confidence: 99%
“…Existem muitas vias que conduzem ao fotoenvelhecimento e esses mecanismos ainda não são muito bem elucidados, porém, sabe-se que a formação de espécies reativas de oxigênio (radicais livres), a indução de metaloproteinases na matriz e o fato de crescimento (TGF-β) refletem aspectos centrais do envelhecimento da pele DOREN, 2015;PITTAYAPRUEK et al,2016;IMOKAWA & ISHIDA, 2015;NEWTON et al,2015;REHMAN, KONDO & SHIMIZU, 2015;TEWARI et al, 2014;LESIAK et al, 2016).…”
Section: Pele E Envelhecimento Cutâneo: Aspectos Geraisunclassified
“…A matriz extracelular é composta principalmente de colágeno I e III, elastina, proteoglicanos e fibronectina. Na pele exposta à radiação UV, podese observar a desorganização das fibras de colágeno, aumento da produção de elastina com depósitos prejudiciais, diminuição da quantidade de colágenio I e III e a junção dermoepidérmica é achatada, além de sua função também ser afetada DOREN, 2015;PITTAYAPRUEK et al,2016;IMOKAWA & ISHIDA, 2015;NEWTON et al,2015;REHMAN, KONDO & SHIMIZU, 2015;TEWARI et al, 2014;LESIAK et al, 2016).…”
Section: Pele E Envelhecimento Cutâneo: Aspectos Geraisunclassified
See 1 more Smart Citation